Feasible sampling plan for adults of Aleurocanthus woglumi Ashby (Hemiptera: Aleyrodidae) in orange orchards - Santana, Alisson da Silva [UNESP]; Lima, Ana Paula Santana [UNESP]; Pinheiro, Aline Marques; Santana, Emile Dayara Rabelo; Nascimento, Luis Fernando de Andrade; Santos, Ane Caroline Celestino; Silva, Jefferson Elias; Bacci, Leandro (Elsevier, 2022)
The success of integrated pest management programs depends on the use of feasible and efficient sampling plans. Considering that the citrus blackfly, Aleurocanthus woglumi Ashby (Hemiptera: Aleyrodidae), is an important citrus pest, the aim of this research was to develop a conventional sampling plan to assess adult populations of this insect in orange orchards. For this, we defined the sampling unit, number of samples, time and the cost of sampling. The third most apical leaf of the branch was the ideal unit to assess citrus blackfly adult densities and the sampling plan consisted of 58 samples. On average, the plan required 55.26 min to complete and costs US$ 1.78. The sampling plan developed here is an accurate, viable and low-cost tool that can be used in integrated pest managemant programs in orange orchards. Our methods can also be applied to study ecological and geographic parameters of this pest.
Keywords: Citrus blackfly; Negative binomial distribution; Number of samples; Sampling unit